Bubble flow configurations generated by ejector type bubble generator - Catrawedarma, I Gusti Ngurah Bagus; Ton, Sefri; Pranowo, Dadang Dwi; Surahmanto, Fredy; Astyanto, Achilleus Hermawan (International Journal of Applied Sciences and Smart Technologies, 2025)
Bubble flow configurations generated by an ejector bubble generator were captured using a high-speed video camera and extracted into several images. The air flow and nozzle diameter were varied during the test in ranges of 0.1-1.5 lpm and 1.17-3.5 mm, respectively. The results reveal that in general the bubble flow structure coming out from the bubble generator is divided into three regions, namely the entrance, bubble swarm, and bubble dispersed region. It is found that there is a higher time delay of bubble production when the air flow and the nozzle diameter decrease. On the other hand, the bubble production time is longer, if the air flow and the nozzle diameter increase.